OPTIMIZING DIGITAL WAQF FOR SUSTAINABLE NATIONAL DEVELOPMENT: PUBLIC POLICY APPROACHES IN INDONESIA - Wulandari, Yunita; M. Naseh, Ahmad; Zaman, Ahmad Zuhairuz; Bukhori, Imam; Febrianti, Andini (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Conventional waqf management often falls short in optimizing the potential of waqf assets to significantly contribute to sustainable national development, particularly amidst rapid digital technological advancements. Traditional management systemslimit the transparency, accountability, and outreach of this form of Islamic philanthropy. This study aims to explore and formulate effective public policy approaches to enhance the digitalization of waqf management in Indonesia. It also examines existing regulatory frameworks and the opportunities to leverage technology in waqf administration. This research adopts a qualitative, library-based method using a normative-juridical approach to analyze various waqf-related regulations in Indonesia. The findings highlight that robust public policies are essential to standardize digital infrastructure, ensure data security, foster public trustin digital waqf, and support nazir in managing waqf assets more effectively. Ultimately, optimizing digital waqf through strategic public policy is crucial for transforming waqf into a dynamic and transparent instrument for sustainable national development.